Degradasi Zat Warna Eriochrome Black-T (EBT) dengan Katalis ZnO-TiO2 menggunakan Metode Sonolisis - Santika Putri; Hary Sanjaya (Jurnal Periodic Jurusan Kimia UNP, 2023)
Eriochrome Black-T (EBT) is a dye that is widely used in the textile industry, dyeing silk, wool, nylon, double fiber and in the laboratory as a complexometric titrant for the estimation of Ca2+, Mg2+ and Zn2+. This EBT dye is dangerous if released into natural waters which can significantly affect the photosynthetic activity of the aquatic environment because its decomposition products such as naphthoquinone are carcinogenic. So, its presence in drinking water and surface water can be deadly. Therefore, the dyestuff is degraded before being discharged into the environment so that the resulting environmental pollution can be described. The purpose of this research is to determine the optimum time and the addition of TiO2 doping on ZnO catalyst for the degradation of EBT by sonolysis method. The percentage of EBT dye degradation was obtained from the absorbance value measured using a UV-Vis spectrophotometer. Absorbance measurements were carried out at the maximum wavelength (λ max) of EBT, which was 535.60 nm. The results showed that the optimum time for EBT degradation was 30 minutes with a degradation percentage of 81.65%. On the effect of variations in the addition of TiO2 doping showed optimum results at ZnO-TiO2 10%  with a degradation percentage of 84.30%.